Prevalence and pathology of colibacillosis in broiler farms at Dinajpur Sadar Upazila (Bangladesh Veterinarian, 2022)
This study was carried out to investigate the prevalence and pathological lesions of avian colibacillosis in commercial broiler farms at Dinajpur Sadar Upazila (Sub-district) from July to December 2018. A total of 8800 birds from six farms were diagnosed with colibacillosis from clinical signs, post-mortem lesions and histopathological changes. Highest prevalence was in F1 farm (76.2%) and lowest in F6 farm (9.2%). Highest mortality was in F1 farm (9.1%) and lowest in F6 farm (3.3%). Average prevalence was 39.6% and mortality 5.4%. Highest prevalence was at0-2 weeks of age (69.3%) and lowest at2-4 weeks of age (9.6%). The most common gross lesions were air sacculitis, omphalitis, pericarditis, perihepatitis, peritonitis and enteritis. The microscopic lesions were haemorrhage and congestion in lung, destruction of intestinal wall and reactive cell infiltration, and thickening of fibrous tissue in pericardium.Bangl. vet. 2021. Vol. 38, No. 1-2, 10–16